2010
DOI: 10.1155/2010/219793
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin Isoinhibitors with Antiproliferative Activity toward Leukemia Cells fromPhaseolus vulgariscv “White Cloud Bean”

Abstract: A purification protocol that comprised ion exchange chromatography on DEAE-cellulose, affinity chromatography on Affi-gel blue gel, ion exchange chromatography on SP-Sepharose, and gel filtration by FPLC on Superdex 75 was complied to isolate two trypsin inhibitors from Phaseolus vulgaris cv “White Cloud Bean”. Both trypsin inhibitors exhibited a molecular mass of 16 kDa and reduced the activity of trypsin with an IC50 value of about 0.6 μM. Dithiothreitol attenuated the trypsin inhibitory activity, signifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Otherwise, the inhibition mechanism of EvTI is different of a Kunitz-type inhibitor PdKI2 from Pithecelobium dumosum seed, which inhibits trypsin by competitive mode [63]. The IC 50 of EvTI for trypsin was 2.2×10 −8 mol.L −1 (0.42 µg.mL −1 ), that was less potent than urinary trypsin inhibitor (IC 50 of 6.44×10 −10 mol.L −1 ) [67], and lower than trypsin inhibitor from Sapindus saponaria seeds L (SSTI2 IC 50 8.3×10 −8 mol.L −1 ), and than purified trypsin inhibitors from Phaseolus vulgaris (IC 50  = 6.0×10 −7 mol.L −1 ) and from Glycine max (IC 50  = 1.9×10 −5 mol.L −1 ) [68], [69]. These results indicate that EvTI is effective on inhibiting trypsin like other inhibitors described in the literature.…”
Section: Discussionsupporting
confidence: 64%
“…Otherwise, the inhibition mechanism of EvTI is different of a Kunitz-type inhibitor PdKI2 from Pithecelobium dumosum seed, which inhibits trypsin by competitive mode [63]. The IC 50 of EvTI for trypsin was 2.2×10 −8 mol.L −1 (0.42 µg.mL −1 ), that was less potent than urinary trypsin inhibitor (IC 50 of 6.44×10 −10 mol.L −1 ) [67], and lower than trypsin inhibitor from Sapindus saponaria seeds L (SSTI2 IC 50 8.3×10 −8 mol.L −1 ), and than purified trypsin inhibitors from Phaseolus vulgaris (IC 50  = 6.0×10 −7 mol.L −1 ) and from Glycine max (IC 50  = 1.9×10 −5 mol.L −1 ) [68], [69]. These results indicate that EvTI is effective on inhibiting trypsin like other inhibitors described in the literature.…”
Section: Discussionsupporting
confidence: 64%
“…From 100 g of small pinto beans, about 141 mg of trypsin inhibitor could be collected using the protocol mentioned above. The yield was higher than that obtained in purification of many other trypsin inhibitors, such as broad bean, white cloud bean and Faba bean trypsin inhibitors ($11, $29 and $54 mg/100 g beans, respectively) [22][23][24] .…”
Section: Discussionmentioning
confidence: 63%
“…The three-step protocol is simpler than purification procedures employed for many other trypsin inhibitors such as white cloud bean trypsin inhibitor 22 . By using fewer purification steps, the loss of the trypsin inhibitor can be minimized, and a higher yield of the protein can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The study also reported that cells treated with TBPI diminished their invasive ability most probably due to the suppression of MMP2 and MMP9. Sun et al (2010) isolated and purified two trypsin inhibitors of each with a molecular mass of 16 kDa from Phaseolus vulgaris cv “White Cloud Bean.” Both of these inhibitors showed an antiproliferative activity toward Leukemia L1210 albeit with a little variance in potency, but there was little activity toward lymphoma MBL2 cells.…”
Section: Roles Of Plant Protease Inhibitors In Health and Disease Conmentioning
confidence: 99%